Renal Disease Patterns: Insights from Native Kidney Biopsies - An Experience at LUMHS - Khalil, Samreen; Kumar, Pooran; Memon, Asfa; Lohana, Aneeta; Habib, Maimoona; Khalil, Shumaila (Indus Journal of Bioscience Research, 2025)
Background: Renal biopsy remains the gold standard for diagnosing biopsy-proven renal disease and can be associated with significant morbidity in adults. The determination of the renal disease spectrum through biopsy has a key role in clinical decision-making, particularly in patients with nephrotic syndrome, nephritic syndrome, acute kidney injury, and chronic kidney injury. The goal of this study is to evaluate the prevalence of renal disease in renal biopsy patients and investigate associated demographic factors. Objective: To assess the prevalence of renal disease in renal biopsy patients at Liaquat University Hospital, Hyderabad. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from December 2024 to March 2025 at the Department of Nephrology, Liaquat University Hospital, Hyderabad. Methodology: A total of 80 patients aged 18-60 years, who underwent renal biopsy for suspected renal disease, were included. Data on demographic factors such as age, gender, socioeconomic status, and comorbidities were collected. Renal biopsy samples were analyzed by senior renal pathologists for histopathological diagnosis. Results: The most prevalent diagnosis was primary glomerulonephritis, found in 50% of the patients, followed by secondary glomerulonephritis (25%), tubulointerstitial diseases (15%), and renal vascular diseases (10%). Hypertension showed a trend towards higher prevalence in PGN (p=0.061). Socioeconomic status was significantly associated with tubulointerstitial diseases (p=0.007). Conclusion: Primary glomerulonephritis is the most prevalent renal disease in our cohort.